2000
DOI: 10.1037/0021-9010.85.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Self-management training for improving job performance: A field experiment involving salespeople.

Abstract: In a control-group field experiment using a reversal design, 30 insurance salespeople were randomly assigned to an experimental group that received self-management training. A multivariate analysis of variance and subsequent repeated-measures analyses of variance revealed that, compared with a control condition (n = 30), training in self-management skills significantly improved job performance as assessed through both objective and subjective measures. Performance improvement continued with time, and increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
161
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(173 citation statements)
references
References 54 publications
5
161
1
6
Order By: Relevance
“…Self-leadership is, however, not a sufficient substitute for external leadership, and Stewart, Courtright, and Manz (2011) identified EL as an important external factor that facilitates employees' self-influencing skills. Previous studies have indicated positive associations between EL and self-leadership (e.g., Tekleab et al, 2008;Yun et al, 2006), whereas in other studies self-leadership has shown positive associations with employee outcomes such as self-efficacy (Prussia, Anderson, & Manz, 1998), job performance (Frayne & Geringer, 2000), and job satisfaction (Neck & Manz, 1996). To the best of our knowledge self-leadership have not yet been investigated as mediator between EL and subordinate outcomes.…”
Section: Central Mediators Of Empowering Leadershipmentioning
confidence: 71%
See 1 more Smart Citation
“…Self-leadership is, however, not a sufficient substitute for external leadership, and Stewart, Courtright, and Manz (2011) identified EL as an important external factor that facilitates employees' self-influencing skills. Previous studies have indicated positive associations between EL and self-leadership (e.g., Tekleab et al, 2008;Yun et al, 2006), whereas in other studies self-leadership has shown positive associations with employee outcomes such as self-efficacy (Prussia, Anderson, & Manz, 1998), job performance (Frayne & Geringer, 2000), and job satisfaction (Neck & Manz, 1996). To the best of our knowledge self-leadership have not yet been investigated as mediator between EL and subordinate outcomes.…”
Section: Central Mediators Of Empowering Leadershipmentioning
confidence: 71%
“…Self-leadership for its part is proposed to affect job performance (e.g., Neck & Houghton, 2006), which previously has been supported empirically (e.g., Frayne & Geringer, 2000). Together with Hypotheses 3 and 4 this forms a model in which EL affected subordinates' job performance through their self-leadership.…”
Section: Studymentioning
confidence: 95%
“…To develop employee capabilities and productivity, the literature notes that employee training is one of the critical HRM practices (Chen et al, 2003;Frayne and Geringer, 2000). At the individual level, training is a process that results in more effective job performance and is characterized by not only the acquisition of new skills, but also by the increased capacity to learn more and to recognize training opportunities (Amit and Belcourt, 1999).…”
Section: Human Resource Managementmentioning
confidence: 99%
“…It is through career management that people can actively get involved in the construction of their "best possible future" (Savickas, 2008, 110). Although it is considered that an increasing number of people might be using this method in their career, this does not mean, however, that all people are, indeed, effective self-managers (Frayne and Geringer, 2000).…”
mentioning
confidence: 99%
“…Self-career management can be translated into a range of cognitive and behavioral strategies (Frayne and Geringer, 2000), developed by each individual, with the purpose of exercising control over their own career goals (Orpen, 1994). It can be defined as a continuous process of solving problems, through which individuals develop a greater awareness about themselves and the world of work (gathering relevant information about their values, interests, skills, strengths and weaknesses, preferred lifestyle, occupations, jobs and business alternatives), identify realistic career goals based on this information, and implement and monitor career strategies that increase the likelihood of achieving these career objectives (e.g., Greenhaus and Callanan, 1994;Kossek et al, 1998;Noe, 1996).…”
mentioning
confidence: 99%